An exploration of the origins of the Malagasy using genetic polymorphisms - Morar, Bharti (My University, 2014)
Malgache, qui es-tn?' This question seeking the ancestry o f the Malagasy remains unanswered five centuries after the debate on the proposed hypotheses of Malagasy origins began. Historical, archaeological, linguistic and some genetic data suggest two major sources o f ancestry: Africa and Indonesia, with minor contributions from Arabia, India and China, but the evidence for the suggestions is sparse and inconclusive. All Malagasy, irrespective of their ethnic backgrounds speak a common language, Malagasy, but differences in physical appearance and culture suggests that they may have different ancestral histories. The goals of this study are to utilize genetic variation present in the Malagasy in conjunction with available data to reconstruct their prehistory and to provide evidence confirming and/or refining existing theories concerning their prehistory. The genetic profiles of eleven of the eighteen Malagasy ethnic groups, a South African Indian and six African populations were compared at thirteen loci; eight autosomal and five Y chromosomal. The markers include four STR loci each on the autosornes (HUMCSF1PO, HUMTH01, HUMCD4 and an (AC)n repeat m the DRD2 gene) and on the Y chromosome (DYS3.93, DYS19, DYS390 and DYS391), two Alu polymorphisms (CD4-/Uw and YAP) and three RtLP loci within the DRD2 gene, Some o f these loci were used to derive autosomal an-j Y chromosome haplotypcs, Population trees as well as principal component analyses- bast-d ba the different data sets consistently revealed very close affinities between the eleven Malagasy groups examined, The intermediate clustering of the Malagasy between African and South Asians also reaffirms that these two groups have contributed significantly to the Malagasy gene pool. Admixture estimates made using autosomal data suggest that approximately 50% o f the Malagasy gene pool is derived from an African source while Y chromosome data indicates an African contribution o f at least 60%. Networks constructed using Y chromosome haplotypes identified a ‘Malagasy-specific’ haplotype cluster. A divergence time of 2864 years (95% confidence intervals, 1227 - 7472 years) is estimated for this cluster which is consistent with archaeological data suggesting that the colonization of Madagascar occurred within the past 3000 years. Both autosomal and Y chromosomal ihta from the present study supports a recent common ancestry for the Malagasy from founders whose gene pool contained contributions from Indonesians and Africans.
Keywords: Polymorphism (Genetics)